Scan QR code or get instant email to install app

Skip to content
#
Simplify the given expression:

\(3+(3-8)^2-7 =\)

### Related Information

Question:

\(3+(3-8)^2-7 =\)

`_________`

.
A
\(21\)

explanation

Apply Order of Operations rules: P is for Parenthesis, and anything in parenthesis should be done first.

Followed by Exponents

Following now is Multiplication and Division, and this is special because it’s not that one needs to be done before the other, these are just worked from left to right.

Finally, Addition and Subtraction work the same way as Multiplication and Division. So, these will also be done from left to right, but these will be the last things done when simplifying an expression.

Our problem: \(3+(3-8)^2-7\)

Subtract: \(3 −8 = −5\).

Apply the exponent: \((-5)^2=25\)

\(= 3 + 25 − 7\)

Subtract: Add the opposite

\(= 3 + 25 + (−7)\)

Add: \(3 + 25 = 28\).

\(= 28 + (−7)\)

Add: \(28 + (−7) = 21\).

Take more free practice tests for other GED topics with our ged test now!

Comments